INVESTIGATION ON ACUTE TOXICITY AND BEHAVIORAL CHANGES IN TILAPIA ZILLII DUE TO GLYPHOSATE-BASED HERBICIDE, FORCEUP - C. D. Nwani; U. A. Ibiam; O. U. Ibiam; O. Nworie; G. Onyishi; C. Atama (Journal of Animal and Plant Sciences, 2013)
Glyphosate, N-(phosphoromethyl) glycine is one of the most widely used herbicide in agriculture for the control of weeds and woody shrubs. A 96 h semi-static acute toxicity bioassay was carried out to determine the LC50 value and behavioral responses of commercial formulation of glyphosate (forceup) on the freshwater fish Tilapia zillii. The 24, 48, 72 and 96 h LC50 values (with 95 % confidence limits) estimated by probit analysis were 477.79 (431.01-558.23), 296.43(265.45-325.52), 253.21(222.58-281.02) and 211.80 (122.27-293.55) mgl-1 respectively. The safe level for the herbicide varied from 2.118 to 2.118×10-3 mgl-1 . Fish exposed to higher concentration of the herbicide showed uncoordinated behavior such as erratic and jerky swimming, attempt to jump out of water, frequent surfacing and gulping of air, decrease opercula movement and secretion of mucus on the body and gills followed by exhaustion and death. Our result though indicate that commercial formulation of glyphosate (Forceup) is mildly toxic to T. zillii, the herbicide should be applied with caution in our environment especially near water bodies to avoid the possible risk associated with the use of the pesticide.
Keywords: Tilapia zillii; glyphosate; toxicity; LC; behavioral changes; safe level